HPV genotyping and risk factors for anal high-risk HPV infection in men who have sex with men from Toronto, Canada - Yoojin Choi (Nature Portfolio, 2021)
Abstract Men who have sex with men (MSM) are disproportionately affected by anal cancer, predominantly caused by high-risk (HR) human papillomavirus (HPV) infection. Currently, the nonavalent HPV vaccine provides coverage against nine HPV genotypes, including seven HR-HPV genotypes. Here, we characterize anal HR-HPV genotype distribution and associated risk factors in MSM from Toronto, Canada recruited between September 2010 and June 2012. Wilcoxon–Mann–Whitney test was used for continuous variables, Chi-square test was performed for categorical variables, and a multivariable model using logistic regression was created to assess for correlates of anal HR-HPV infection. A total of 442 MSM were recruited, with a median age of 45 (IQR 38–50) and an overall HPV prevalence of 82%. The prevalence of any HR-HPV infection was 65.3% and 50.7% in the HIV-positive and HIV-negative MSM, respectively. No participant tested positive for all genotypes covered by the nonavalent vaccine. HIV status (aOR 1.806; 95% CI 1.159–2.816), smoking (aOR 2.176; 95% CI 1.285–3.685) and the number of lifetime sexual partners (aOR 2.466; 95% CI 1.092–5.567) were independent risk factors for anal HR-HPV infection. Our findings will be useful to inform HPV vaccine rollout and HPV prevention strategies in Canadian MSM.